Analisis Tingkat Kemiskinan dan Perekonomian di Myanmar - Tata Ihsan; Embun Afifah Honey; Jacky Wardhana; Rangga Arya Prasetia; Mega Amanda; Yusawinur Barella (Journal of Management and Social Sciences, 2025)
Poverty is a major issue faced by developing countries, including Myanmar. This article analyzes the level of poverty and economic factors affecting these conditions in Myanmar. Using a qualitative approach with literature review methods, this study collects secondary data from various literatures, reports, and previous research. The findings indicate that poverty in Myanmar is exacerbated by factors such as political instability, ineffective economic policies, and prolonged internal conflicts. The military coup and the COVID-19 pandemic have significantly reduced economic growth, increased poverty rates, and worsened living conditions. Additionally, international sanctions and the decline in bilateral aid have contributed to the ongoing economic crisis. The role of the United Nations Development Programme (UNDP) and the Association of Southeast Asian Nations (ASEAN) in addressing poverty in Myanmar is a crucial focus of this study. The study concludes that collective efforts from various parties are necessary to address poverty in Myanmar through economic policy reforms, political stability improvements, and sustained international aid.